Impact of Classroom Environment on High School Students’ Mathematics Anxiety - Paudel, Krishna Chandra (Academic Journal of Mathematics Education, 2023)
This study is aimed at identifying the relationship between classroom environment and mathematics anxiety of students. Adopting a quantitative data analysis procedure, it has been revealed that there exists a significant negative correlation for the scales for teacher’s support and learning mathematics anxiety and mathematics evaluation anxiety. It has also been identified that learning environment scales and learning mathematics anxiety include significant, negative and independent relationships in relation to teacher’s support, investigation, task orientation and equity. Acknowledging teachers as catalysts in pedagogical practice, the study shows that they can play a pivotal role in easing mathematics learning byreducing mathematics anxiety.